1999
DOI: 10.1006/viro.1999.9663
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4 Open Reading Frame 4-Induced Dephosphorylation Inhibits E1A Activation of the E2 Promoter and E2F-1-Mediated Transactivation Independently of the Retinoblastoma Tumor Suppressor Protein

Abstract: Previous studies have shown that the cell cycle-regulated E2F transcription factor is subjected to both positive and negative control by phosphorylation. Here we show that in transient transfection experiments, adenovirus E1A activation of the viral E2 promoter is abrogated by coexpression of the viral E4 open reading frame 4 (E4-ORF4) protein. This effect does not to require the retinoblastoma protein that previously has been shown to regulate E2F activity. The inhibitory activity of E4-ORF4 appears to be spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
2
22
0
2
Order By: Relevance
“…It has been shown that E4orf4 leads to the reduced phosphorylation of different proteins either involved in transcription, or splicing. 83,[87][88][89] The E4orf4-PP2a complex leads to hypophosphorylation of transcription factors c-Fos, E4F, and regulates their transcriptional activity, however, the kinases targeted by the E4orf4-PP2A complex in this process is not known. The complex of E4orf4 also leads to reduced phosphorylation of serine/arginine-rich (SR) proteins, which inhibits IIIA pre-mRNA splicing.…”
Section: E4orf4-another Tumor-selective Killermentioning
confidence: 99%
“…It has been shown that E4orf4 leads to the reduced phosphorylation of different proteins either involved in transcription, or splicing. 83,[87][88][89] The E4orf4-PP2a complex leads to hypophosphorylation of transcription factors c-Fos, E4F, and regulates their transcriptional activity, however, the kinases targeted by the E4orf4-PP2A complex in this process is not known. The complex of E4orf4 also leads to reduced phosphorylation of serine/arginine-rich (SR) proteins, which inhibits IIIA pre-mRNA splicing.…”
Section: E4orf4-another Tumor-selective Killermentioning
confidence: 99%
“…2 protein is a multifunctional viral regulator, which down-regulates expression of genes that have been activated by E1A and cAMP (1)(2)(3)(4), induces hypophosphorylation of various viral and cellular proteins (1,5), regulates alternative splicing of adenovirus mRNAs (5), and induces p53-independent apoptosis in transformed cells (6 -8). Oncogenic transformation of primary cells sensitizes them to cell killing by E4orf4 (9), indicating that E4orf4 research may have exciting implications for cancer therapy.…”
Section: Adenovirus E4orf4mentioning
confidence: 99%
“…he adenovirus E4orf4 protein contributes to the progression of viral infection from the early to the late phase (1)(2)(3)(4)(5)(6)(7). When expressed outside the context of virus infection, E4orf4 induces caspase-and p53-independent cell death in transformed cells (34,37,39,42).…”
mentioning
confidence: 99%